Factors influencing cloud computing adoption in Malaysian information technology companies - Mohammadi, Alireza; Saeedikondori, Armin; Ali, Noor Azman (Faculty of Economics and Management, Universiti Putra Malaysia, 2017)
Cloud computing is one of the most popular technology and service and its usage growth has increased in recent years. The purpose of this study is to understand the factors, which influence the adoption of cloud computing by Malaysian Information Technology (IT) companies. The eight independent variables, which are examined in this study, are relative advantage, complexity, compatibility, top management support, firm size, technology readiness, competitive pressure and trading partner pressure. The sample size of this research is 50 IT experts from different IT companies in Malaysia whom may or may not implement cloud computing. The questionnaire considered as a tool for collecting data, contains two parts; the first part is the descriptive part and the second part is questions about the variables. The finding of the study showed that relative advantage, compatibility, top management support and competitive pressure have a significant effect on cloud computing adoption. The study contributes to the application of new technology of cloud computing adoption in the high-tech industry through the use of a wide range of variables. The results also help companies consider their information technologies investment when implementing cloud computing. The research framework hypothesized the relationship of eight factors with cloud computing adoption in Malaysian IT companies, and from the results, it is revealed that these factors are influencing cloud computing adoption by 69.1%, and the most important factor is relative advantage by 33.6%.